ASSESMENT OF PHYSICOCHEMICAL PARAMETRS OF DADIN KOWA DAM, NIGERIA - Muhammad, Kabiru; Haruna Saidu; Muhammed, Ishaku (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
The assessment of the water quality criteria of Dadin Kowa reservoir based on some selected physicochemical parameters were carried out over a period of twelve months. Five sampling stations were chosen for the study. Water sample for analysis was collected from reservoir of Dadin Kowa Dam and analyzed insitu for physicochemical parameters based on standard methods. These parameters include water temperature, pH, transparency, nitrate, hardness, biochemical oxygen demand, phosphate, calcium, iron and magnesium. All the physicochemical parameters revealed monthly and seasonal variations. The result of the physicochemical parameters obtained from this study was compared with standard values set by World Health Organization (WHO). Overall assessment revealed that, the results of the physicochemical parameters were within the standard safe limit set by WHO. Moreover, some sampling stations that showed slight increase in value of parameters was reported to be influenced by anthropogenic activities such as washing of clothes and application of fertilizers and pesticides. This study showed that the reservoir of Dadin Kowa is suitable for irrigational and domestic purposes. In order to improve the sustainable use of the reservoir, appropriate suggestions were provided on how to safeguard the healthy status of the reservoir for wider scope of usage.